Myxopapillary ependymoma of the posterior mediastinum - Estrozi, Bruna [UNESP]; Queiroga, Eduardo [UNESP]; Bacchi, Carlos E. [UNESP]; Faria Soares de Almeida, Virginia; Lucas de Carvalho, Jose; Lageman, Gerritt M.; Rosado-de-Christenson, Melissa; Suster, Saul (Elsevier, 2006)
A left paravertebral mass discovered incidentally on routine examination in a 39-year-old woman is described. Computerized tomography studies revealed a 7 × 6 cm, well circumscribed, noncalcified soft tissue mass with lobular borders abutting the left inferior pulmonary vein and descending aorta. It was not possible to determine the exact anatomic location of the mass based on the imaging studies as both peripheral lung tumors and posterior mediastinal lesions may exhibit the imaging findings described here. At thoracotomy, the mass was seen to be well circumscribed, focally attached to the pleura but without involvement of lung parenchyma, and situated in the left posterior mediastinum. On histological examination, the lesion showed the classical features of myxopapillary ependymoma. Immunohistochemical studies confirmed this impression by demonstrating strong positivity of the tumor cells for S-100 protein, glial fibrillary acidic protein, and CD99 and negative staining with other differentiation markers. A review of the literature with a discussion of the histologic and radiologic differential diagnosis of these lesions is presented. © 2006 Elsevier Inc. All rights reserved.
Keywords: Central nervous system; Myxopapillary ependymoma; Tumor; CD99 antigen; glial fibrillary acidic protein; protein S 100; adult; case report; central nervous system; computer assisted tomography; descending aorta; diagnostic imaging; differential diagnosis; ependymoma; female; histopathology; human; image analysis; immunohistochemistry; mediastinum tumor; medical examination; priority journal; pulmonary vein; soft tissue tumor; thoracotomy; Adult; Antigens, CD; Cell Adhesion Molecules; Diagnosis, Differential; Ependymoma; Female; Gene Expression Regulation, Neoplastic; Glial Fibrillary Acidic Protein; Humans; Mediastinal Neoplasms; S100 Proteins; Tomography, X-Ray Computed